REVISION SISTEMATICA, ANALISIS CLADISTICO Y BIOGEOGRAFIA HISTORICA DE LOS GENEROS FALKLANDIUS ENDERLEIN Y LANTERIELLA GEN. NOV. (COLEOPTERA: CURCULIONIDAE) - Morrone, Juan J. (Acta Entomológica Chilena, 2022)
The gcnus Falklandius Enderlein (Curculionidae: Rhytirrhininae: Listroderini) comprises five species (3 ncw described in this contribution) inhabiting the Falkland Islands, Tierra del Fuego, and Magallanes. The genus is redescribed, descriptions and illustrations of its species are presented, and a key for their identificalion is provided. The genus Lanteriella, most closely related to Falklandius, is described for the endogean species L. microphtalma spec. nov. A cladislic analysis of the species of Falklandius is perforined, using 27 characters from external morphology, body vestiture and male and female genitalia. In the most parsimonious cladogram, of 33 steps and a consistency Índex of 0.68, the species follow the sequence F. antárcticas (Stierlin), F. turbificatus Enderlein, F. goliath spec. nov., F. kitscheli spec. nov., and F. magellanicus spec. nov. A panbiogeographic analysis is applied to Falklandius and other animal and plant taxa (totalyzing 50) distributed in the Falkland Islands, Tierra del Fuego, Magallanes, and various subantarctic islands. This analysis establishes that different generalized tracks overlap in the Falkland Islands and Tierra del Fuego, identifying these areas as nodes.